Towards A One World Development Path: the Case for Grassroots Development - Stefano Zamagni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
After a brief description of the diversity of development experiences in the post-warperiod, the paper considers the three most important lessons stemming from those experiences. An explanation of the contrast between grassroots and macro development performance is then offered together with a characterization of the notion of participatory development as a launching pad for a new development impulse. The paper concludes with a defence of publication as a precondition for the starting up of a one-world development path.
Keywords: 330